(untitled) (Tzintzun, Revista de Estudios Históricos, 2020)
This article analyzes the works of Father Agustin Rivera on the subject of the novohispanic higher education and his inheritance. He was an avid critic of the practices of educational institutions, of the absence of modern science, as well as of â€œfalse scholasticismâ€. He vindicated the scholastic method and training based on the reading of Latin classics. Renowned as a liberalist, his work brings us closer to the complexity of that category in the subject of education and its relationship with the religious.